2016
DOI: 10.1136/jnnp-2016-313918
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral glucose metabolism and cognition in newly diagnosed Parkinson's disease: ICICLE-PD study

Abstract: Objective To assess reductions of cerebral glucose metabolism in Parkinson's disease (PD) with 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET), and their associations with cognitive decline. Methods FDG-PET was performed on a cohort of 79 patients with newly diagnosed PD (mean disease duration 8 months) and 20 unrelated controls. PD participants were scanned while on their usual dopaminergic medication. Cognitive testing was performed at baseline, and after 18 months using the Cognitive Drug Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 44 publications
7
55
1
2
Order By: Relevance
“…Interestingly, hypometabolism on 18 F-FDG PET preceded spatially matching atrophic changes on MRI (103). Across the entire group of patients with PD, PD-MCI, or PDD, regional glucose metabolism correlated with memory and visuospatial functions in the posterior temporal and parietal regions and also with attentional, executive, and language functions in the frontal regions (88,98). Several additional clinical observations support the strong negative prognostic value of posterior cortical hypometabolism.…”
Section: F-fdg Pet Imaging Of Cognitive Impairment In Pdmentioning
confidence: 69%
See 2 more Smart Citations
“…Interestingly, hypometabolism on 18 F-FDG PET preceded spatially matching atrophic changes on MRI (103). Across the entire group of patients with PD, PD-MCI, or PDD, regional glucose metabolism correlated with memory and visuospatial functions in the posterior temporal and parietal regions and also with attentional, executive, and language functions in the frontal regions (88,98). Several additional clinical observations support the strong negative prognostic value of posterior cortical hypometabolism.…”
Section: F-fdg Pet Imaging Of Cognitive Impairment In Pdmentioning
confidence: 69%
“…Patients with MCI typically exhibit decreased temporoparietal, occipital, precuneal, and frontal metabolism when compared with healthy controls and, to a lesser extent, PD patients without MCI (88,91,98,101,102). These changes were more pronounced in multidomain than single-domain MCI (91,102).…”
Section: F-fdg Pet Imaging Of Cognitive Impairment In Pdmentioning
confidence: 91%
See 1 more Smart Citation
“…These results suggest that the increased RT in the LBD group is a result of delayed onset of task related cognitive activity, and hence slower processing. These regions are all affected in LBD, with metabolic reductions in the occipital and parietal lobes (Firbank et al, ; Kantarci et al, ), reports of reduced grey matter in the insula (Blanc et al, ; Xu et al, ) and cholinergic (Mazère et al, ) and dopaminergic (O'Brien et al, ) alterations in the BG.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging biomarker studies of cognitive impairment in PD have targeted neurotransmitter systems, pathological protein deposits, and glucose metabolic or perfusion changes. Prospective evaluation of glucose metabolic changes have shown that incident dementia initially may present as a predominant hypometabolic posterior cortical pathology involving the visual association cortex, inferior parietal and temporal regions, the posterior cingulum, and precuneus in PD . Subsequent progression to dementia is associated with mixed subcortical, including the thalamus and caudate nuclei, and widespread cortical changes that involve the anterior cortices as well .…”
Section: Mild Cognitive Impairment and Dementia In Pdmentioning
confidence: 99%